Dietary Wolffia arrhiza meal as a substitute for soybean meal: its effects on the productive performance and egg quality of laying Japanese quails - Suppadit T. (2014)
Wolffia arrhiza meal (WAM) was evaluated as a protein replacement for soybean meal (SBM) in the diet of laying Japanese quails. A total of 480 4-week-old laying quails were randomly allocated to form six groups in a completely randomized design. Each group contained four replicates, with 20 quails per replicate. WAM was incorporated into the diets at levels of 0, 4.00, 8.00, 12.0, 16.0 and 20.0%. The results showed that feed intake per bird per day, daily egg-laying rate, feed cost per 100 egg weight, egg width, egg length, egg weight, eggshell thickness, yolk height and shell quality characteristics in terms of breaking time, Young's modulus, work, maximum force, fracturability, breaking stress, stiffness and power showed no statistically significant differences (P > 0.05) among the 0 to 16.0% levels of WAM. However, these performance measures were significantly lower with 20.0% WAM in the formulated ration (P < 0.05). Mortality showed no significant differences among dietary treatments (P > 0.05). The color intensity of the yolk increased as SBM was replaced with increasing amounts of WAM (P < 0.05). In conclusion, WAM could be successfully used in place of SBM. However, the amount used should not exceed 16.0%. © 2012 Springer Science+Business Media B.V.